Patogenisitas Jamur Entomopatogen Metarhizium Anisopliae Metch. Terhadap Larva Spodoptera Litura F. Pada Tanaman Kubis (Brassicae Oleracea L.) Di Laboratorium - Salasa, Tirsa; Tarore, Dantje; Rimbing, Jimmy (Sam Ratulangi University, 2024)
This study aims to analyze the pathogenicity of the entomopathogenic fungus M. anisopliae in infecting S. litura. The research was conducted over a period of 3 months, from February to May 2024. It took place at the Kalasey Biological Agents Laboratory, Balai Perlindungan dan Pengujian Mutu Tanaman Pangan dan Hortikultura (BPPMTPH) in North Sulawesi Province. The study employed a Completely Randomized Design (CRD) with 4 treatments, each replicated 4 times. The number of samples per replication was 20 larvae, resulting in a total of 80 larvae per treatment. Data were analyzed using probit analysis and ANOVA followed by Least Significance Different (LSD) test at a 5% significance level. The results indicated that the pathogenicity of the entomopathogenic fungus M. anisopliae could infect S. litura larvae as early as one day after application. The concentration of 108 conidia/ml was highly effective, achieving 100% mortality within 6 days of application. The fastest LT50 value was observed at the concentration of 108 conidia/ml, which required only 2.8 days, while the LC50 value was found at a concentration of 107.6 conidia/ml.